Mesotherapy using dutasteride‐containing preparation in treatment of female pattern hair loss: photographic, morphometric and ultrustructural evaluation. (6th April 2012) - Moftah, N.; Moftah, N.; Abd‐Elaziz, G.; Ahmed, N.; Hamed, Y.; Ghannam, B.; Ibrahim, M.
Abstract Background Treatment of female pattern hair loss (FPHL) is frustrating for both patients and doctors. Mesotherapy is a novel treatment for hair fall and its efficacy in FPHL has not been evaluated. Objective Evaluation of the efficacy and safety of mesotherapy using dutasteride‐containing preparation in treatment of FPHL. Methods This study included 126 female patients with FPHL. They were classified into two groups; group I (86 patients) injected with dutasteride‐containing preparation and group II (40 control patients) injected with saline. Patients received 12 sessions and were evaluated at the 18th week by: photographic assessment, hair pull test, hair diameter and patient self‐assessment. Ultrastructural evaluation was done for three patients. Results After mesotherapy with dutasteride‐containing preparation, photographic improvement occurred in 62.8% of patients compared with 17.5% in control group (P < 0.05), mean number of epilated hairs was significantly decreased (P < 0.05), mean hair diameter was significantly increased (P < 0.05). Patient self‐assessment showed statistically significant improvement compared with the controls (P < 0.05). There was a negative correlation between degree of improvement and duration of FPHL (P < 0.05). Side effects were minimal with no statistically significant difference between the two groups (P > 0.05). Ultrastructural examination of pretreated hairs revealed absent cuticle in one patient and focal destruction of the cuticle in the second patient, which reappeared in both after therapy. Conclusion We concluded that mesotherapy with dutasteride‐containing preparation was effective, tolerable and minimally invasive treatment modality in FPHL with better response for shorter duration of the disease.